Fatty Oils from Oilseeds of Forest Origin as Antibacterial agents - Jain, P. P.; Suri, R. K.; Deshmukh, S. K.; Mathur, K. C. (Indian Forester, 1987)
Fatty oils extracted from seed of Cassia tora Linn., Wrightia tomentosa Roem &Schult., Viburnum coriaceum Blume, Michelia champaca Linn., Pongamia pinnato and Azadirachta indica A Juss., have been tested in vitro against five species of bacteria i.e. Bacillus pumilus Gottheil, Bacillus subtilis Cohn, Salmonella typhosa (Zopf) white syn. Salmonella typhi Warren and Scott., S paratyphi (Kayer) Casteliani and Chalmers and Micrococcus pyogens var. albus (Rosenbach, Schroeten) Syn. Staphylococcus albus Rosenbach. Present investigations reveal that all the above mentioned fatty oils have potent antibacterial efficay against Bacillus subtilis, Salmonella typhosa and S paratyphi.